Honorary Doctorate Dr. Souha Kanj - Kanj, Souha (Radboud University Press, 2023)
On 15 October 2020, in the middle of the COVID-19 pandemic, Dr. Souha Kanj received a Radboud honorary doctorate in recognition of her achievements in the field of infection control and prevention, efforts in antimicrobial stewardship, and research on various infectious diseases, particularly antimicrobial resistant (AMR) bacteria. This edition includes the laudatio and the speech of our honorary doctor. Kanj published the first overview of antibiotic resistance in Arab countries and discovered differences between neighboring countries in the epidemiology of antimicrobial resistance. She also developed infection prevention monitoring and education programs for healthcare workers, and private organizations in the Arab world. Thanks to her efforts, Lebanon has signed the WHO pledge for hand hygiene. Kanj is not only commended for her expertise, didactic skills, and contribution to medicine, but also for her resilience and strong belief in making a positive impact, despite the difficult journey she has been through, having studied during the Lebanese civil war and being faced with numerous challenges that hit Lebanon and the region after that.